PELATIHAN PENGISIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN BAGI GURU SMKN 2 BANJARMASIN - Julkawait, Julkawait; Nikmah, Nailiya; Safrina, Noor; Salman, Putriana (Politeknik Negeri Banjarmasin, 2021)
Reporting taxes today does not take long with technological sophistication. One of them is using the e-Filing method. With this method, not only tax reporting for personal taxpayers but also appropriate for corporate taxpayers who wish to carry out their tax obligations more easily. How to report electronic SPT online through the DJP Online website set by the government, is contained in the latest regulation, Minister of Finance Regulation (PMK) RI Number 9 / PMK.03 / 2018. Time and cost efficiency is guaranteed because taxpayers no longer need to come and queue at the tax office to report their SPT. Online SPT reports are certainly easier to use. Especially for entrepreneurs who do not have a background in taxation studies. The e-Filing application provided even comes with a guide. So, if you find obstacles or difficulties in filling in the Taxpayer's data, you can see this guide. The output planned in this community service proposal is a journal community service of Banjarmasin State Polytechnic. The method to be carried out is training by providing counseling or guidance on filling out the Annual Tax Return (SPT) and training / practice filling out the SPT with a laptop or computer that has been prepared.